O Gombrowiczowskim kiczu w kontekście teorii (po)nowoczesności - Jaszewska, Dagmara (Załącznik Kulturoznawczy, 2023)
The article develops the researches started by Jerzy Jarzębski; it discusses the phenomenon of kitsch in the work of Witold Gombrowicz. The study is based on a content analysis of selected fragments of works by this author (especially the novel under the title “Ferdydurke”) and it refers to the selected concepts of modernity and postmodernity (W. Welsch, R. Rorty, J. Baudrillard). The writer himself is treated as an original philosopher of modernity (and later – postmodernity – thanks to this, he was ahead of his time). The work presents the thesis that we can assign to Gombrowicz – both the modernist sense of the category of kitsch and practices of its parody, as well as a peculiar tendency to kitsch and a tendency to play with kitsch. This tendency is analyzed in the article as an attitude corresponding with a postmodern condition, especially with its characteristic phenomenon called the aesthetization of culture, which was mentioned, among other things, by Wolfgang Welsch (culture of design, gadget and uperficial styling). Philosophy of Gombrowicz in this sense corresponds with the postmodern rehabilitation of kitsch.